Patients' perception towards nurse caring behaviours in adult medical wards in Hospital Universiti Sains Malaysia (HUSM) - Ali, Norliza (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Caring is an essence and central focus in nursing and become an important element in delivering a good nursing care to patients. The purpose of this study was to identify the relationship between gender and patients' perception of important nurse caring behaviour at adult medical wards in HUSM. Watson's theory of human ~ring was used as a theoretical framework for this study. The Caring Behaviours Assessment instrument is a 63 items questionnaire and used a Likert-type summation scale. Data was collected using self-administered questionnaire. The response rate was 51.20%. The results of the study revealed that, "check my condition very closely" (m = 4.40} as the single most important behaviour by the nurses to indicate a sense of caring by the patients. The finding of this study also revealed Human Needs Assistance (m =4.18} as the most important subscale and this correlates with the results of other similar studies using the CBA tool. However, this study showed no association between gender and their perception towards nurse caring behaviour p= 0.792 which the value of p> 0.05. Similar with several previous studies, respondents considered technical competence to be the most important nurse caring behaviour, which further the emphasizes the notion of caring as a moral stance integral to all interactions with patients.